A Study to Evaluate Stress Level and Coping Strategies among Cancer Patients Undergoing Chemotherapy - Sarwar, Sabiha; Imdad, Parveen; Shah, Fasiha; Samar, Victoria; Qureshi, Irum; Syed, Binafsha Manzoor (Indus Journal of Bioscience Research, 2025)
Background: Cancer continues to be a major cause of death worldwide, posing a significant challenge to efforts aimed at increasing life expectancy globally. Chemotherapy being one of the common methods of treating cancer has many side effects that psychologically affect the patients. Some coping strategies have implications for patients’ perception of their illness, and therefore influence their mental health and quality of life. Aim of study: To assess stress level among cancer patients undergoing chemotherapy and coping strategy they use to overcome the stress. Material and Methods: An analytical cross-sectional study was carried out on 330 cancer patients at Medical Research Centre, Liaquat University of Medical & Health Sciences, Jamshoro, Pakistan and cancer patients were recruited from NIMRA, Hospital Jamshoro. Data was collected through a questionnaire with Three components, Part 1 covered Patients’ demographic and disease-related information, Patients' stress levels are assessed in Part 2 using the Post-Traumatic Stress Evaluation Scale (PCL-C), and participants' coping mechanisms are assessed in Part 3 using the Brief- Coping Orientation to Problems Experienced Inventory (COPE) inventory, consists of 28-point to measure the person's coping styles. Results: A total of 330 participants were enrolled in the study age ranged from 19 to 75 years (median age = 41-60). The mean score of the study subjects was 46.04 ± 10.75. Levels of stress assessed through PCL-C scale, showed a significant variation in stress levels. The majority of participants reported experiencing severe stress, with 54.8% (n = 181) indicating that they faced considerable stress. Three distinct coping strategies adopted by participants with highest mean score (23.58) was seen for the Dysfunctional coping followed by Emotion focused with mean score (22.63) and Problem focused coping with mean score (15.12). Conclusion: Chemotherapy considerably raises patients' stress levels. Coping mechanisms, including emotion-focused and problem-focused approaches, were found to be useful in reducing stress.